Response Time Relationship Time Nurse with Success Cardiac Arrest Patient Management in the Emergency Unit - Asrianto Asrianto; Rosida Rosida; Rahmat Pannyiwi (International Journal of Health Sciences, 2025)
Background: Cardiac arrest is an emergency that requires immediate and appropriate treatment. One key factor in the success of cardiopulmonary resuscitation (CPR) is the speed of response of nurses in the Emergency Department (ER). Response time Fast time) is associated with an increased chance of successful treatment of cardiac arrest patients. Objective: This study aims to determine the relationship between nurse response time and the success of treating cardiac arrest patients in the ER. Methods: This study used an observational analytical design with a cross-sectional approach. The sample was 40 cardiac arrest patients treated in the Emergency Department of Hospital "X" during the period of January–June 2025. Measurements were made on the nurses' response time from patient identification to the start of CPR. The success of treatment was measured by the presence of a return to normal. of spontaneous circulation (ROSC). Data analysis was performed using the Chi- Square test using a significance level of 0.05. Results: The results of the study showed that most nurses with a response time of ≤1 minute successfully increased the ROSC rate in cardiac arrest patients compared to nurses with a response time of >1 minute. The Chi- Square test showed a significant relationship between nurse response time and successful treatment of cardiac arrest patients (p < 0.05). Conclusion: Nurse response time is significantly associated with the success of cardiac arrest treatment in the emergency department. The faster the response, the higher the chance of successful resuscitation.